Evaluation of composite restorations in primary molars subjected to selective caries removal associated with antimicrobial photodynamic therapy: A randomized controlled trial - Faria, Laís Veiga; Antunes, Leonardo Santos; Pio, Luciana Ribeiro Reis; Dias, Jessica Coelho; Pinheiro, Liz Helena Moraes; Reis, Caio Luiz Bitencourt; Fontes, Karla Bianca Fernandes Costa; Cajazeira, Marlus Roberto Rodrigues; Antunes, Lívia Azeredo Alves (International journal of paediatric dentistry, 2022)
Background Antimicrobial photodynamic therapy (aPDT) has been used as an adjunct treatment of deep caries lesions; however, studies on the effects of aPDT on the longevity of restorations are still limited. Aim To evaluate the clinical performance of composite restorations in primary molars subjected to selective caries removal (SCR) associated with aPDT. Design A randomized clinical trial was designed. Primary molars of patients (mean age 6.15 years) with deep caries lesions without signs and symptoms of pulpal involvement were selected. A total of 64 teeth were randomly divided into groups G1 (SCR, 32 teeth) and G2 (SCR + aPDT, 32 teeth) for treatment, restored with composite, and evaluated after a week (T0), 6 months (T1), and 12 months (T2) according to the criteria of FDI. Groups were compared using the Rao‐Scott chi‐squared test and the logistic regression analysis for complex designs to account for multiple observations per subject (alpha = 0.05). Results From all FDI criteria evaluated, the marginal adaptation for the SCR + aPDT group was significantly better in comparison with the SCR group at T0 and T2 in the logistic regression analysis (T0: OR = 0.151; 95% CI = 0.03‐0.068, P = .015; and T2: OR = 0.201; 95% CI = 0.05‐0.79, P = .022). Conclusion The marginal adaptation of primary molar resin restorations was positively affected by aPDT after 12 months of follow‐up.